Teaching Model for Socio-Cultural Knowledge Delivery in Igbo Language - Ngozi L, Dom-Anyanwu; Joy O, Odewumi; Dayo, Akanmu (International Journal of Educational and Psychological Sciences, 2024)
Socio-cultural knowledge simple means the social norms, values and behaviors of a given society and how these norms and values are achieved through the language of the people.  On the other hand, model of knowledge delivery is a design that can perfectly deliver the social and cultural values to the young ones of for cultural existence and identification status.  This paper therefore looks into the models that can deliver Igbo language and culture in a socio-cultural situation.  It comes up with teaching methods like dramatization, traditional and community language learning methods in looking into the challenges of Igbo language and cultural learning.  The methods encourage active participation of the learners in a learner friendly situation hence interactive.  The model blends Igbo cultural concepts in the teaching and learning lessons where the learners would be fully involved through puzzle, games, story-telling and role play.  The main objectives of this study include; the exposure of the children and youths to Igbo culture, to encourage them to use the culture in the social context for easy identification as well as to maintain the culture of the Igbo society. The study adopts Lev Vygotsky’s Socio-cultural theory of 1978.  The study concludes by looking at the contributions of teaching and learning with good strategies in Igbo language for better understanding of the language and culture.